Staff Development: A Study Into The Significance of Staff Professional Development Programs for Educators and Students Achievement - Hamshari, Eman Rasmi (2011)
The concept of staff professional development and its effectiveness has been a key area of discussion for long. Several authors/ researchers have made an attempt to touch upon the different dimensions associated with PD programs. This dissertation attempts to study the significance of staff professional development for educators and how it can affect students’ achievement. Literature review conducted puts forth the rationale for such research work. In this context, various models of staff development have been discussed along with pros and cons. Moreover, in order to induce the teachers with an incentive to actively participate in staff development, role of leaders as motivators has been highlighted. The job is only half done if PD programs are implemented but not assessed to identify how it affects student’s learning. Therefore, considerate importance is given to discuss how the PD program can be made actionable. The primary data collected via survey at schools has been conducted to highlight the perspectives of school regarding such programs in the region. In addition, this dissertation attempts to provide guidelines to educators on how to define PDPs, their execution and their assessment for improvements. After careful analysis of response from principals, it was identified that student learning via PDPs is considered an essential activity by schools in this region. Unfortunately, the end results of such programs are not as effective as desired for several reasons. One of those critical reasons is lack of planning in conducting such programs, i.e. path of execution, aims of programs and evaluation mechanisms are unclear. On the other hand, there is a strong motivation registered from teachers, which is playing a role in getting teachers to undertake such programs or become part of such activities. Leaders of schools in this region are in the process of identifying how to appropriately use PDPs as motivational tools for teachers to achieve improvement in learning.